NURSES AND PHYSICIANS IN THE FAMILY HEALTH STRATEGY: WORKLOADS AND COPING - Denise Elvira Pires de Pires; Elaine Cristina Novatzki Forte; Thayse Aparecida Palhano de Melo; Carolina Neis Machado; Camila Duarte de Castro; Felipa Rafaela Amadigi (Universidade Federal do Paraná, 2020)
Objective: To analyze factors that increase and reduce workloads of the FHS nurses and physicians and to identify coping strategies. Method: A qualitative study conducted through semi-structured interviews in the five regions of Brazil. The participants were 27 nurses and 21 physicians, in the period from January 2017 to June 2019. Thematic content analysis was performed with the ATLAS.ti 8 software. Results: The factors that increase the loads were excess demand, work overload, and failures in work conditions, organization, and management. Teamwork, planning, bonding with health care services users, and resoluteness of care help to reduce the loads. For coping with the loads, physical activity and disconnection from work stand out. Conclusion: Elements that increase the loads prevailed; however, characteristics of the care model contribute to their reduction. The identification of loads is essential and contributes to the planning of coping actions.